2010
DOI: 10.1002/etc.191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changes in analytical techniques for the measurement of polychlorinated biphenyls and organochlorine pesticides on temporal trends in herring gull eggs

Abstract: Changes in analytical approaches during the tenure of monitoring programs for organochlorine (OC) pesticides and polychlorinated biphenyls (PCBs) may affect estimates of temporal trends. We used an in-house reference material to create multiplication factors to adjust the estimates of OC pesticides and PCBs (Aroclor equivalents) in Great Lake herring gull eggs analyzed using electron capture detection (1987-1997) to be more equivalent to estimates using mass spectrometric detection (1998-2005) as well as accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A positive value indicates that mercury concentrations rose significantly at the change point year, and a negative value indicates that mercury concentrations declined significantly at the change point year (Pekarik and Weseloh 1998;de Solla et al 2010). Change point regressions were performed using an analysis module in WILDSPACE TM (Wong et al 2003).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A positive value indicates that mercury concentrations rose significantly at the change point year, and a negative value indicates that mercury concentrations declined significantly at the change point year (Pekarik and Weseloh 1998;de Solla et al 2010). Change point regressions were performed using an analysis module in WILDSPACE TM (Wong et al 2003).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Wild birds in captivity or in experiments, or studies with values other than wet weight reporting, or those expressed on a lipid basis, or of individual birds, were not included. There have been improvements in analytical techniques for environmental contaminants over the last decades that in some cases dictate a correction factor to compare temporal trends, particularly prior to the 1980s, 130 but this facet has not been approached by us. A total of 164 publications since 1960 were found that reported levels of one or more of the constituents of the 5 groups of environmental contaminants in blood; 127 were in whole blood, 36 in plasma and one in serum.…”
Section: The Database Of Exposure Valuesmentioning
confidence: 99%